2017
DOI: 10.1177/0260106017704797
|View full text |Cite
|
Sign up to set email alerts
|

Selected weight management interventions for military populations in the United States: a narrative report

Abstract: Overweight and obesity continues to be a significant public health burden in the US and particularly among military personnel. Although the US Department of Defense mandates standardized physical activity requirements for military members, incidence and prevalence of overweight and obesity among military personnel continue to increase. Each military department controls their own interventional strategies for physical fitness and weight control. However, unique challenges such as geographic transients, lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…The effectiveness of the weight loss interventions was also found to be significant largely in active-duty military personnel but not in veterans. These findings indicate that weight management interventions in the military population are effective, updating previous research [20,65,89]. Most of the included interventions were based on behavior change strategies adopting a comprehensive approach with different therapeutic goals, combining lifestyle modification with diet and nutritional changes and physical activity therapy, in line with previous evidence [20].…”
Section: Discussionsupporting
confidence: 82%
“…The effectiveness of the weight loss interventions was also found to be significant largely in active-duty military personnel but not in veterans. These findings indicate that weight management interventions in the military population are effective, updating previous research [20,65,89]. Most of the included interventions were based on behavior change strategies adopting a comprehensive approach with different therapeutic goals, combining lifestyle modification with diet and nutritional changes and physical activity therapy, in line with previous evidence [20].…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, a review of 8 lifestyle programs in military populations showed that most did not result in significant weight loss at 6 months post-intervention. 13 However, a recent study comparing counselor initiated and self-paced adaptations of the LookAHEAD Intensive Lifestyle Intervention program in AD personnel showed that both interventions produced significant weight loss and decrease in abdominal circumference. 14…”
Section: Purposementioning
confidence: 99%
“…Research on the determinants of eating behaviors in military populations appears to be limited to topics such as sociodemographic characteristics of overweight and obesity within military populations (e.g., Hruby et al, 2015; Sanderson et al, 2014); the role of nutritional supplements and the composition and delivery of ration packs for training and combat missions (Crombie et al, 2013; Tassone & Baker, 2017). Eating behaviors have been examined as part of large-scale interventions to combat overweight and obesity that rely on a limited number of tools such as cognitive behavioral counseling, education and are based on minimal use of theory for program development, implementation, and evaluation (Murray et al, 2017). To date, only a handful of studies (e.g., Carins et al, 2016; Carins & Rundle-Thiele, 2014a; 2014b; Kullen et al, 2016) have examined the determinants of eating behaviors or tested and evaluated programs that aim to improve eating behaviors in military populations specifically.…”
Section: Background and Literaturementioning
confidence: 99%